2022
DOI: 10.3390/md20120760
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived Actinomycetes: Biodegradation of Plastics and Formation of PHA Bioplastics—A Circular Bioeconomy Approach

Abstract: Plastics are present in the majority of daily-use products worldwide. Due to society’s production and consumption patterns, plastics are accumulating in the environment, causing global pollution issues and intergenerational impacts. Our work aims to contribute to the development of solutions and sustainable methods to mitigate this pressing problem, focusing on the ability of marine-derived actinomycetes to accelerate plastics biodegradation and produce polyhydroxyalkanoates (PHAs), which are biodegradable bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…It was also found that the crystallinity of PBAT exposed to aqueous environment did not change after UV treatment [44]. In addition, the contribution of microorganisms to the degradation of BPs cannot be ignored, as they secrete various enzymes that can effi ciently promote the degradation of BPs, and studies have shown that with the radiation of UV could achieved a better degradation eff ect [45,46]. In fact, whether exposure to UV radiation in the natural environment is suffi cient to enhance biodegradation remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the crystallinity of PBAT exposed to aqueous environment did not change after UV treatment [44]. In addition, the contribution of microorganisms to the degradation of BPs cannot be ignored, as they secrete various enzymes that can effi ciently promote the degradation of BPs, and studies have shown that with the radiation of UV could achieved a better degradation eff ect [45,46]. In fact, whether exposure to UV radiation in the natural environment is suffi cient to enhance biodegradation remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Gordonia sihwensis , Gordonia mangrovi , and Gordonia bronchialis isolated from mangroves showed PS degradability with 4.69–7.73% degradation rates in one month [ 73 ]. Srreptomyces gougerotti , Micromonospora matsumotoense , and Nocardiopsis prasina isolated from the ocean could degrade LDPE, PS, and polylactic acid (PLA) to varying degrees [ 77 ].…”
Section: Microbial Degradation Of Plasticsmentioning
confidence: 99%
“…PS is the fifth mostly used synthetic polymer 93,94 in packaging materials, food containers and construction materials. 95,96,97 PS is an aromatic thermoplastic with a C-C backbone, 81 makes its biodegradation very difficult.…”
Section: Ps Mechanism Biodegradationmentioning
confidence: 99%